The Alexandria Library and the Work of the International Friends - Alan Hopkinson; Neslihan Burcu Akdağ (Bilgi Dünyası, 2004)
The Alexandria Library is well known, less known is the work of the International Friends. International friends’ groups have been set up with support from UNESCO. The original library’s origins and how it met its end are obscure. The rebuilding of the new library concluded with its being opened in 2002. An acquisitions policy is in place and materials are provided with support from Friends. looking to the future the library is hosting a mirror of the Internet Archive.